The necessity of morphological awareness for science undergraduates - Namal, W.; Wickramasekera, M. (University of Jaffna, 2018)
Vocabulary is one of the most essential components of language. Without an adequate vocabulary, some undergraduates who enter the faculties that use English medium instruction, struggle to achieve academic success.After analysing the undergraduates’ performances at English examinations in the Faculty of Science, it was realized that the low proficiency students lack the threshold level of vocabulary to express their ideas, to write sentences using morphological and syntactic rules correctly.Consequently, this study was conducted with the objective of improving the vocabulary volume of low proficiency undergraduates in the Faculty of Science where the medium of instruction is English, in order for them to read, listen and write more effectively in English. This would help the undergraduates with their academic work as well as future goals. The theoretical framework of this study is morphological awareness, the ability to reflect on and manipulate morpheme - the smallest unit of meaning in words in developing English vocabulary. This was a quasi- experimental study with a quantitative, qualitative mixed method. The data samplein this research was randomly selected 60 low proficiency first year undergraduates. The sample was divided into two groups, the control group and the experimental group. A test was given as two items; a morpheme identification test and a morphological structure awareness test. It was administered before and after intervention. The intervention was carried out with the experimental group, and the control group only received the lesson material. Results indicated that morphological awareness had significantly improved the use of vocabulary among low proficiency undergraduates. Furthermore, the findings indicated that the morphological knowledge is helpful for the undergraduates to analyse words and write grammatically correct sentences. In conclusion, findings imply a need to give more emphasis to increase the morphological knowledge when preparing English for Academic Purposes lessons to the undergraduates who follow English medium instruction.
Keywords: English medium instruction; Morphemes; Morphological awareness; Vocabulary